Glycosphingolipids and Infection. Potential New Therapeutic Avenues - Aerts, Johannes M. F. G.; Artola, M.; van Eijk, M.; Ferraz, M. J.; Boot, R. G. (Frontiers in Cell and Developmental Biology, 2019)
Glycosphingolipids, the main topic of this review, are a subclass of sphingolipids. They are ubiquitous in the outer leaflet of the plasma membrane of cells with their glycans facing the extracellular space. Glycosphingolipids are implicated in a variety of biological processes including specific infections. Various types of pathogens exploit glycosphingolipids of host cells as membrane receptors. In addition, lipid-rafts of host cells can act as platforms for infection signaling. Relatively common in man are inherited deficiencies in lysosomal glycosidases involved in the turnover of glycosphingolipids. The associated storage disorders (glycosphingolipidoses) are characterized by the accumulation of substrates of the deficient enzyme in lysosomes. In recent years compounds have been identified that allow modulation of glycosphingolipids levels in cells. Some of these agents are well tolerated and already used to treat lysosomal glycosphingolipidoses. This review summarizes present knowledge on the role of glycosphingolipids in infection and subsequent immune response. It concludes with the thought to apply glycosphingolipid-lowering agents to prevent and/or combat infections.